EFFECTIVENESS OF CONTINUOUS PROFESSIONAL DEVELOPMENT TO IMPROVE TEACHING: EVIDENCE-BASED ON SYSTEMATIC REVIEW - Amna Saleem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Continuous professional development is indispensable for updating and upgrading the teachers and to cope with rapid changes in the social and educational environment. Continuous professional development enhances the teacher’s competence in their classrooms. This study endeavors to investigate the impact of continuous professional development on the teacher’s performance. The researcher has collected data from various online sources such as Google scholar and online available journals. The researcher employed content analysis for reviewing related research articles. Most of the articles are qualitative that were reviewed and utilized by the researcher. The research was concluded with the key outcomes that exposed the effectiveness of continuous professional development and described that continuous professional development will be more effective and impactful if it’sstructured is developed properly and according to the needs of teachers. It is suggested future researcher should conduct this type of systematic review to find out the hurdles which conducting authority is facing in its implementation process.